ANALISA PENGARUH LAJU ALIRAN PARTIKEL PADAT TERHADAP SUDU-SUDU TURBIN REAKSI PADA SISTEM PEMBANGKIT LISTRIK TENAGA UAP MENGGUNAKAN CFD - Hariri Dwi Kusuma; MSK. Tony Suryo Utomo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2014)
A good quality of steam is essentially needed on power plant system. The main function of this steam is to rotate steam turbine and to couple generator for produce electric. The use of the steam bean is very risky because of the relatively high velocity fluid that comes out of the previous step due to the narrowing of the flow. High velocity may cause huge turbulence which affects the rate of erosion in steam turbine blade. The purpose of this study is to determine the effect of effect of mass flow rate of solid particle of the fluid toward the erosion rate in the blade using CFD. Variations of the mass flow rate of solid particle are 1 kg/s, 1,2 kg/s, 1,4 kg/s, 1,6 kg/s, 1,8 kg/s, and 2 kg/s. Simulation results shows that the increased mass flow rate of solid particle affects to the increasing the erosion rate.